2012
DOI: 10.1517/14728214.2012.691965
|View full text |Cite
|
Sign up to set email alerts
|

Emerging drugs for Duchenne muscular dystrophy

Abstract: Introduction Duchenne muscular dystrophy (DMD) is the most common, severe childhood form of muscular dystrophy. Treatment is limited to glucocorticoids that have the benefit of prolonging ambulation by approximately 2 years and preventing scoliosis. Finding a more satisfactory treatment should focus on maintaining long-term efficacy with a minimal side effect profile. Areas covered Authors discuss different therapeutic strategies that have been used in pre-clinical and clinical settings. Expert opinion Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 130 publications
1
62
0
Order By: Relevance
“…In skeletal muscle the impact of ROS is physiologically well contained through the activation of an endogenous program of antioxidant response, including the expression of redox-sensitive transcription factors [68][69][70][71]. However, elevated levels of free radicals generated under pathologic conditions can overwhelm the antioxidant defense leading to protein carbonylation and DNA damage.…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In skeletal muscle the impact of ROS is physiologically well contained through the activation of an endogenous program of antioxidant response, including the expression of redox-sensitive transcription factors [68][69][70][71]. However, elevated levels of free radicals generated under pathologic conditions can overwhelm the antioxidant defense leading to protein carbonylation and DNA damage.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Moreover, antioxidant drugs can be an important therapeutic option to counteract the secondary signs of dystrophinopathy [68]. Clinical studies using the synthetic derivative of coenzyme Q10, namely idebenone, revealed the efficacy of antioxidant drugs for DMD treatment.…”
Section: Therapeutic Approaches Direct Against Pathogenic Mechanisms mentioning
confidence: 99%
“…http://dx.doi.org/10.1101/012344 doi: bioRxiv preprint first posted online Dec. 8, 2014; In addition to corticosteroids, there are a number of therapies and clinical trials in development based on the tremendous knowledge about DMD pathophysiology [15].…”
Section: Cc-by-nd 40 International License Peer-reviewed) Is the Autmentioning
confidence: 99%
“…Additional targets include the reduction of inflammation or the promotion of skeletal muscle blood flow and muscle contractility using nitric oxide (NO) donors [14].…”
Section: Discussionmentioning
confidence: 99%